2018
DOI: 10.1111/ffe.12866
|View full text |Cite
|
Sign up to set email alerts
|

High cycle fatigue analysis in the presence of autofrettage compressive residual stress

Abstract: An experimental and numerical investigation of the effect of residual compressive stress on the high cycle fatigue life of notched low carbon steel test specimens is presented. Experimentally determined cyclic stress strain curves for S355 low carbon steel are utilized in a finite element analysis plasticity modelling framework incorporating a new cyclic plasticity material model representative of cyclic hardening and softening, cyclic mean stress relaxation, and ratcheting behaviors. Fatigue test results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…to Sellen et al 6 for 6082 and Repplinger et al 7 for 6061). No sign of mean stress relaxation was observed, but cyclic loading may result in a shift of the residual stress field 24 . The FE material model should fully include the cyclic material characteristics.…”
Section: Mechanical Materials Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…to Sellen et al 6 for 6082 and Repplinger et al 7 for 6061). No sign of mean stress relaxation was observed, but cyclic loading may result in a shift of the residual stress field 24 . The FE material model should fully include the cyclic material characteristics.…”
Section: Mechanical Materials Modelmentioning
confidence: 95%
“…Common residual stress measurement techniques for metals are based upon non‐destructive X‐ray diffraction or on the destructive incremental hole‐drilling method combined with strain determination 23 . Okorokov et al 24 used a prestressed, notched tensile test specimen of the material S355 to analyze stress relaxation during axial cyclic loading, thus clarifying the complexity depending on the geometry, material response, nature, and magnitude of loading. Fatigue tests showed that the fatigue life of a component not only depends on the magnitude of induced compressive residual stress but also on cyclical hardening and plastic strain accumulation during high cycle fatigue loading.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…An inspiring fatigue prediction method of parts subjected to an autofrettage process described the work [11].…”
Section: Review Of Literaturementioning
confidence: 99%